Game-based Networked Learning - Castañeda, Linda; Villar-Onrubia, Daniel; Haba-Ortuno, Inmaculada; Postigo-Fuentes, Ana Yara; Arnab, Sylvester (Proceedings of the International Conference on Networked Learning, 2024)
Designing and analyzing learning experiences in non-formal contexts can be challenging, even for those with educational training. The challenge is more significant if the priorities include educational ideological bases or an specific type of educational vision. The DALI project (Data Literacy for Citizens) has the primary goal of offering Data Literacy learning experiences specifically designed for adults in non-formal educational contexts. With this goal in mind, and considering the social and material realities of the target participants –their needs, diversity, interests and cultures– the project combines two of the most promising pedagogical approaches nowadays: networked learning and playful learning. This short paper outlines the pedagogical vision underpinning our efforts to integrate both approaches into a set of strategies and resources, in other words, the principles and ideas driving the design of what is called in the project: Game-based Networked Learning (GBNL) experiences. In particular, we draw on both the Activity Centred Analysis and Design (ACAD) framework and the Transdisciplinary Model for Developing Game-Based Interventions. After reviewing key aspects of the theoretical grounds that define our understanding of educational uses of technology and game-based learning, the paper addresses critical considerations underpinning the adaptation of the ACAD framework in the planning of playful learning experiences. Thus, the paper outlines the main principles guiding the design of DALI experiences, dividing them into the three design areas established by ACAD: set design, epistemic design and social design. The ambition of this approach is to serve as a pedagogical and educational statement to guide valuable actions to improve other adult learning approaches.